STRATEGI INOVATIF DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA MENGGUNAKAN PENDEKATAN PEMBELAJARAN AKTIF DAN KOLABORATIF DI ERA DIGITAL - Silfah Bena; Serpin Lele Siduruk; Dela Yanti Mangiri'; Erlan Oktavia; Sandra Menong (CV. Adiba Aisha Amira, 2025)
Increasing student learning motivation is a major challenge in the world of education, especially in the digital era which is full of distractions. This article aims to explore innovative strategies in increasing student learning motivation through active and collaborative learning approaches. This approach involves students directly in the learning process, facilitates interaction between students, and encourages collaboration in solving problems. The use of digital technology as a means of supporting learning, such as online learning platforms and educational social media, also increases student engagement. This research shows that active and collaborative learning can motivate students to participate more, develop critical thinking skills, and improve learning outcomes. By integrating technology, teachers can create a learning environment that is interesting and relevant to students' needs in the digital era. Therefore, implementing this strategy is expected to increase student motivation and overall quality of learning.